Literature Review : Non-Pharmacological Therapy for Pain Reduction in Cancer Patients - Kai, Meggy Wulandari; Utami, drg. Naning Kisworo; Kai, Mohamad Nur Fadjri (JURNAL CITRA KEPERAWATAN, 2025)
Cancer is a disease characterized by the uncontrolled proliferation of aberrant cells in the body. This uncontrolled cell development can harm regular cells around it and elsewhere in the body. Pain management in breast cancer patients can be applied pharmacological (therapy with drugs) and nonpharmacological (complementary therapy). The goal of this study is to determine whether non-pharmacological therapy may be employed to reduce pain in cancer patients. The type of research used is a literature review, where data from the same study is grouped based on the measured results. A series of keyword models are used to conduct literature searches using Google Scholar. Journal searches are limited from 2018 to 2024. From the search results obtained, the articles found were then checked for articles that could be accessed from 2018 to 2024, and 70 articles were found according to the research theme. After the selection stage of research articles, twenty articles were selected that met the inclusion and exclusion criteria of the research with an experimental study design. Based on the findings of the literature study, it was found that the types of non-pharmacological therapies that can be done to reduce pain in cancer patients such as Slow Stroke Back Massage Technique, Benson Relaxation, Virtual Reality Therapy, Acupressure, Murotal Therapy Al-Qur'an and Dhikr, Classical Masase, Transcranial Magnetic Stimulation (TMS) Action, Five Finger Relaxation, Guided Imagery Relaxation with Lavender Aromatherapy, Respiratory Relaxation and SEFT Therapy, Combination of Progressive Muscle Relaxation (PMR) and Guided Imagery, as well as Music and Hypnotherapy.